Clinical usefulness of dopamine transporter SPECT imaging with 123I-FP-CIT in patients with possible dementia with Lewy bodies: Randomised study. (February 2015) - Walker, Zuzana; Moreno, Emilio; Thomas, Alan; Inglis, Fraser; Tabet, Naji; Rainer, Michael; Pizzolato, Gilberto; Padovani, Alessandro
Abstract : Background: Dementia with Lewy bodies (DLB) is underrecognised in clinical settings. Aims: To investigate whether performing a 123 I-ioflupane injection ( 123 I-FP-CIT also called DaTSCAN TM ) single photon emission computed tomography (SPECT) scan in patients with possible DLB would lead to a more certain diagnosis (probable DLB or non-DLB dementia). Method: We randomised 187 patients with possible DLB 2:1 to have a scan or not (control group). The outcome measure was a change in diagnosis to probable DLB or non-DLB. Results: There were 56 controls and 114 scanned patients, of whom 43% had an abnormal scan. More patients in the imaging group had a change in diagnosis compared with controls at 8 and 24 weeks (61% ( n = 70) v. 4% ( n = 2) and 71% ( n = 77) v. 16% ( n = 9); both P <0.0001). Clinicians were more likely to change the diagnosis if the scan was abnormal (82%) than if it was normal (46%). Conclusions: Imaging significantly contributed to a more certain diagnosis, proving to be a useful adjunct in the work-up of patients with possible DLB.